2021
DOI: 10.1021/acs.jafc.1c01537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Major Allergen in Buckwheat Seeds: Fag t 6

Abstract: Buckwheat is one of the five main allergenic foods (eggs, milk, wheat, buckwheat, and peanuts). Oleosin is an important type of allergen in some allergic foods. However, although most diagnostic nut and seed extracts are defatted, some patients with food allergies may have false negative diagnostic results of oleosin in vitro. Recently, we found that the serum of buckwheat allergic patients responded strongly to an 18 kDa protein. Mass spectrometry analysis showed it is the oleosin protein family. We further p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It was shown that roasting increased IgE binding to peanut oleosins 1236 and hazelnut oleosins. [1236,1578,1590] Hazelnut (Corylis avellana) [62,1588,1589] Sesame (Sesamum indicum) [1593,1600] Tartarian buckwheat (Fagopyrum tataricum) [1591,1592] In addition, nonallergic individuals also had IgE to sesame oleosins, which is different for peanut oleosins that were only recognized by IgE in sera from patients with severe peanut allergy. 1236 Up to 30% of sesame allergic patients cannot be diagnosed by routine allergy diagnostic tests, and according to Ehlers and co-workers, they will at present not profit from the addition of Ses i 4 and Ses i 5 to the diagnostic allergen panel.…”
Section: Synthesismentioning
confidence: 99%
“…It was shown that roasting increased IgE binding to peanut oleosins 1236 and hazelnut oleosins. [1236,1578,1590] Hazelnut (Corylis avellana) [62,1588,1589] Sesame (Sesamum indicum) [1593,1600] Tartarian buckwheat (Fagopyrum tataricum) [1591,1592] In addition, nonallergic individuals also had IgE to sesame oleosins, which is different for peanut oleosins that were only recognized by IgE in sera from patients with severe peanut allergy. 1236 Up to 30% of sesame allergic patients cannot be diagnosed by routine allergy diagnostic tests, and according to Ehlers and co-workers, they will at present not profit from the addition of Ses i 4 and Ses i 5 to the diagnostic allergen panel.…”
Section: Synthesismentioning
confidence: 99%
“…However, they are food allergens from four species; four of them are peanuts allergens, three of them are hazelnut allergens, and two are sesame allergens. The Tartarian buckwheat (Fagopyrum tataricum (L.) Gaertn) allergen Fag t 6 is a recent addition to the oleosin allergen family [147]. Oleosins are one of the main classes of proteins associated with plant oil bodies [148].…”
Section: Food Allergensmentioning
confidence: 99%
“…Allergy to quinoa seed seems to be rare with very few case reports in the literature, whereas common buckwheat is a known cause of allergy, being more prevalent in Asia where it is eaten regularly, and often linked to severe and anaphylactic reactions [74]. In addition, an oleosin has recently been identified as a potential causative allergen for reactions to tartary buckwheat ( Fagopyrum tataricum ), usually ingested in the form of buckwheat tea in North Asia and China [75]. Buckwheat allergy is less common in Europe, although a case report from Spain highlighted the issue that, due to its increasing use, buckwheat will undoubtedly become a growing cause of anaphylaxis in Western countries [76].…”
Section: Seedsmentioning
confidence: 99%